2016
DOI: 10.5539/jel.v6n1p1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 5E Inquiry Learning Activities on Achievement and Attitude toward Chemistry

Abstract: The purpose of this study was to investigate the effects of 5E inquiry learning activities on students’ achievement, attitude toward chemistry. A non-equivalent control group design was used to the quasi-experimental research in this study. A total of 34 (8 males and 26 females) undergraduates in Turkey voluntarily participated in the study. The 5E Inquiry Learning Activities were applied to the experimental group and lecture-based traditional activities were applied to the control group. The both two groups w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 28 publications
5
21
1
4
Order By: Relevance
“…It suggested that the students in this group neither had a positive nor negative attitude towards science. The results affirmed the finding of Zeidan & Jayosi (2015) that most students have a neutral attitude towards science and parallel to the findings of Sen & Oskay (2017) that inquiry-based strategy using the 5E"s learning cycle has no significant effect on the attitude of the students.…”
Section:  Results and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It suggested that the students in this group neither had a positive nor negative attitude towards science. The results affirmed the finding of Zeidan & Jayosi (2015) that most students have a neutral attitude towards science and parallel to the findings of Sen & Oskay (2017) that inquiry-based strategy using the 5E"s learning cycle has no significant effect on the attitude of the students.…”
Section:  Results and Discussionsupporting
confidence: 83%
“…This conveyed that the use of inquiry-based strategy using the 5E"s learning cycle did not significantly affect the attitude of the students towards science. This was similar to the finding of Sen & Oskay (2017) that the use of 5E"s learning cycle in teaching does not significantly influence the attitude of the students due to the negative perceptions that the students have concerning the strategy. Another reason for this could be the fact that although students look forward to performing experiments with the use of the 5E"s learning cycle, Demirbaş & Pektaş (2015) asserted that there still students who encounter difficulty in performing investigations.…”
Section: Groupsupporting
confidence: 88%
See 1 more Smart Citation
“…Experiencing Physics through inquiry approaches has also resulted in positive learning attitudes (Lindsay, Hsu, Taylor, Sadaghiani & Cummings, 2012;Salter & Atkins, 2013;Wang et al, 2015). On the contrary, Sen and Oskay (2016) found no significant difference in the cognitive and affective attitudes of students between students exposed to the traditional method of teaching and inquiry approach.…”
Section: Introductionmentioning
confidence: 86%
“…The main technical inquiry learning activities are the maximum involvement of students in the process of learning activities, and the maximum direction of activities in the learning process and students can develop a confident attitude about what is found in the inquiry learning process [18] Inquiry learning models can increase students' confidence in the ability to find solutions from the subject matter given [19]. In the inquiry learning process students work like scientists and find answers to questions and problems through their own research [20][21]. Inquiry learning allows students to actively participate and gain hands-on experience, they learn by asking questions, collecting and processing the data they have collected, and using it to find answers to these questions [22].…”
Section: E Inquiry Learning Model Inquirymentioning
confidence: 99%